2015
DOI: 10.1002/erv.2350
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining Diagnostic Differences Among Exercise and Weight Suppression in Bulimia Nervosa and Binge Eating Disorder

Abstract: Our results suggest that exercise frequency may contribute to different weight suppression outcomes among BN and BED. This may inform clinical implications of exercise in these disorders. Specifically, much understanding of the differences among exercise frequency and the compensatory use of exercise in BN and BED is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We suggested in the Introduction that this would be the case because taking into account individuals' age and height (along with sex) at the time they reached their highest premorbid weight should make the DWS calculation a more sensitive indicator of the discrepancy that WS is meant to reflect. Many past studies have suggested that the larger this discrepancy—as assessed by the traditional WS calculation—the greater the biological (Berner et al., 2017; Bodell & Keel, 2015; Keel et al., 2017; Piers et al., 2019), psychological (Zanetti et al., 2013), behavioural (Bodell & Keel, 2015; Butryn et al., 2011; Cook et al., 2015) and prognostic (Bodell et al., 2017; Lowe et al., 2011) impact on disordered eating. This study examined, for the first time, if the method used to quantify the discrepancy WS is meant to reflect influences the relation between weight suppression and diverse characteristics related to BN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggested in the Introduction that this would be the case because taking into account individuals' age and height (along with sex) at the time they reached their highest premorbid weight should make the DWS calculation a more sensitive indicator of the discrepancy that WS is meant to reflect. Many past studies have suggested that the larger this discrepancy—as assessed by the traditional WS calculation—the greater the biological (Berner et al., 2017; Bodell & Keel, 2015; Keel et al., 2017; Piers et al., 2019), psychological (Zanetti et al., 2013), behavioural (Bodell & Keel, 2015; Butryn et al., 2011; Cook et al., 2015) and prognostic (Bodell et al., 2017; Lowe et al., 2011) impact on disordered eating. This study examined, for the first time, if the method used to quantify the discrepancy WS is meant to reflect influences the relation between weight suppression and diverse characteristics related to BN.…”
Section: Discussionmentioning
confidence: 99%
“…WS has been most often studied among individuals with bulimia nervosa (BN), who often lose a substantial amount of weight in the process of developing their eating disorder (Garner & Fairburn, 1988). Among individuals with BN, higher WS has demonstrated associations with greater binge/purge symptomatology (Butryn et al., 2011; Lowe et al., 2007), future weight gain (Hessler et al., 2018; Lowe et al., 2006; Piers et al., 2019), poorer treatment response (Butryn et al., 2006), greater weight/shape concerns (Accurso et al., 2016), lower leptin levels (Bodell & Keel, 2015; Keel et al., 2017), greater exercise frequency and intensity (Cook et al., 2015), higher body dissatisfaction (Burnette et al., 2018; Zanetti et al., 2013), initial development of anorexia nervosa (AN), BN and purging disorder (Stice et al., 2020) and longer duration of illness (Keel et al., 2017; for a review, see Lowe et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we did only had follow‐up duration for a subset of patients, and we did not retest the previously shown role of WS in determining time to response (Lowe et al, ). Fifth, we did not measure exercise as potential moderator of results, yet it has been shown to contribute to WS in BN (Cook et al, ). Sixth, the present study is exploratory, and results should be replicated in further studies; until then, conclusions remain tentative.…”
Section: Discussionmentioning
confidence: 99%
“…Only one investigation of WS and ED pathology in a mixed-diagnostic sample (in this case, individuals diagnosed with BN or BED) has studied WS as an outcome variable. Cook et al (2015) found that both exercise frequency and BN/BED diagnoses were associated with WS. Additionally, exercise frequency moderated the relation between diagnosis and WS, such that WS was higher in BN than in BED amongst those who reported lower exercise frequency.…”
Section: Weight Suppression and Associated Outcomesmentioning
confidence: 92%
“…Whilst the long-term goal of dieting is sustained weight loss, WS may have both adaptive and maladaptive associations with factors related to weight management in non-clinical populations. Individuals high in WS report higher levels of dietary restraint (Lowe, 1984), increased levels of physical activity (Cook et al, 2015; French & Jeffrey, 1997), and reduced food consumption following a laboratory preload than their counterparts with low WS (Lowe & Kleifield, 1988), which may be adaptive for weight-management-related health outcomes. However, WS has also predicted detrimental eating and weight outcomes in healthy populations, including excess weight gain (Stice, Durant, Burger, & Schoeller, 2011) and more frequent loss of control (LOC) and binge eating behaviour (Van Son, Van Der Meer, & Van Furth, 2013).…”
Section: Weight Suppression and Associated Outcomesmentioning
confidence: 99%